Macromia siamensis, a new species from North Thailand (Odonata: Anisoptera: Macromiidae) - Makbun, Noppadon (Zootaxa, 2022)
Macromia siamensis sp. nov., is described and illustrated based on male specimens collected from Ban Luang, Chom Thong, Chiang Mai province, Thailand. Macromia siamensis sp. nov. shares the hammer-shaped tip of posterior hamulus with M. amphigena Selys, 1871, M. sombui Vick, 1988, M. cydippe Laidlaw, 1922, M. vangviengensis Yokoi et Mitamura, 2002, M. clio Ris, 1916, M. malleifera Lieftinck, 1955, and M. macula Zhou, Wang, Shuai & Liu, 1994, but it differs from all of the mentioned species by a set of coloration characters including antehumeral stripe, abdominal pattern and facial markings.